Mussel: a potential pollution indicator in the aquatic ecosystem and effect of climate change - Atasaral, Şebnem Şahin; Dürrani, Ömerhan; Terzi, Yahya; Seyhan, Kadır (My University, 2020)
The study of ecological indicators, defining and establishing the means of measuring the health of the environment, is of greatimportance. The most important elements of ecosystems are the biological components, and environmental impact assessment ofecosystems will therefore require that these components are seriously laid out. It is, for example, not sufficient to assess the waterquality by the use of physicochemical parameters, although their determination can be carried out much more rapidly. There exists, ingeneral, a relation between species composition and water quality. It is well known that mussels are extensively utilized as abiological indicator of pollution of both marine and freshwater ecosystems. The reason is that the mussel is a sessile, filter-feeding,and able to accumulate within its tissues many of the contaminants. In addition, mussels show a wide geographical distribution asthey permit the survey of extensive coastal and inland areas. The contaminants accumulated in the tissues of mussels may cause a“stress syndrome” with alteration to their physiology. On the other hand, global warming does affect the pH level, especially themarine water resulting increase in acidity. This can be the outcome of the existing genetic variation in natural populations of mussels.They because allow themselves to adapt to declining pH levels in the aquatic ecosystem caused by carbon emissions. We, therefore,focus on the factors that possibly affect the mussel biodiversity in aquatic ecosystems in relation to climate change as well aspollution concerned.
Keywords: Çevre Bilimleri; Deniz ve Tatlı Su Biyolojisi